Between Multicultural Students, Speech Act, and Politeness - Munawwir Hadiwijaya; Maya Rizki Amalyasari (Fakultas Bahasa dan Seni UNP, 2022)
This study aims to reveal the use of directive speech acts of multicultural students studying in Malang City in the context of politeness. Qualitative descriptive is the method used in this study. There are five tribes that are the subject of this research, namely Java, Sumba, Flores, Dayak, and Madura. Data were collected by using questionnaires, interviews, and observations. The data obtained were analysed based on how they used directive request speech act in different situations in the domain of family, friendship, and school and how they minimized the FTA that might occurs when facing different speech partners. The results of this study indicate that from the four aspects that become the parameters of this study, multicultural students in using directive speech acts have the following pattern: In the aspect of direct / indirect speech acts, in three different domains, all multicultural students use direct speech acts, as well as in the honorific aspect. The use of hedge aspects is more widely used in the campus domain. Meanwhile, in the aspect of speech level, only Javanese and Madurese students use it.